2016
DOI: 10.1111/1462-2920.13265
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic resistance pattern of Salmonella serovars in integrated crop‐livestock farms and their products sold in local markets

Abstract: Major concern in the Mixed Crop-Livestock (MCL) farms, in which livestock and vegetables grown closely in the same facility, is cross-contamination of zoonotic bacterial pathogens especially Salmonella. To investigate the distribution of Salmonella serovars in MCL and their products, a total of 1287 pre-harvest samples from various farms and 1377 post-harvest samples from retail supermarkets in Maryland and Washington D.C. areas were collected and analysed. A total of 315 Salmonella isolates were recovered, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 46 publications
(54 reference statements)
3
56
1
Order By: Relevance
“…In most cases, Salmonella infections are associated with diarrhea, weight loss, dramatic alterations in composition of blood cells, as well as death [12,4042]. Accordantly we detected 10 5 -10 7 CFU intestinal colonization of ST induced salmonellosis and caused around 8% weight loss, 52% higher level of RBC, 19% and 71% lower levels of WBC (especially neutrophils and lymphocytes) and PLT, and severe cecal inflammation in the survival mice.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In most cases, Salmonella infections are associated with diarrhea, weight loss, dramatic alterations in composition of blood cells, as well as death [12,4042]. Accordantly we detected 10 5 -10 7 CFU intestinal colonization of ST induced salmonellosis and caused around 8% weight loss, 52% higher level of RBC, 19% and 71% lower levels of WBC (especially neutrophils and lymphocytes) and PLT, and severe cecal inflammation in the survival mice.…”
Section: Discussionsupporting
confidence: 76%
“…Salmonella and diarrheagenic Escherichia coli generally infect human gut intestine through consumption of contaminated foods and/or drinks [1012]. Once these Gram-negative enteric pathogenic bacteria arrive in host gut, their complex type III secretion systems are activated, enabling them to introduce effector proteins directly into cell cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated the potential for Salmonella risks with both conventional and mixed crop-livestock (MCL) farm systems. A higher overall prevalence of Salmonella contamination was detected in the MCL system, whereas multiantibiotic resistance in Salmonella was found predominantly in conventional farms, where farmers are allowed to use synthetic antibiotics, and in their related postharvest products in retail stores (25). In this study, we further investigated phylogenetically inferred relatedness, genomic characteristics, and the alteration of antibiotic resistance-related genes under environmental pressures of the designated S. Typhimurium isolates.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that pasture/organic farming cannot meet the demand for animal products for seven billion people. Furthermore, solely blocking or withdrawing subtherapeutic antibiotic use in animal farming without controlling therapeutic or higher doses of antibiotics and use of other chemicals might not be enough to mitigate the threat of rising rates of antibiotic-resistant zoonotic pathogenic bacteria (9,25,26). According to published data from the Centers for Disease Control and Prevention (CDC), multidrug resistance in Salmonella accounts for approximately 6,200 cases (10% of total) of Salmonella infections each year in the United States.…”
mentioning
confidence: 99%
“…Early detection and management of potentially pathogenic Salmonella spp. is an essential step towards prevention and management of Salmonellosis (Peng et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%